Multiple Small Bowel Perforations in a Patient of Chronic Myeloid Leukemia on Imatinib - Tadaiya, Mahavir Virendra Kumar; Tankshali, Rajen A (Indian Journal of Medical and Paediatric Oncology, 2020)
Chronic myeloid leukemia (CML) is a clonal hematopoietic disorder caused by an acquired genetic defect in a pluripotent stem cell. A series of discoveries led to the recognition that the BCR-ABL protein, which results from a reciprocal translocation involving chromosomes 9 and 22, has a central role in the pathogenesis of chronic myelogenous leukemia. The BCR-ABL protein functions as a constitutively activated tyrosine kinase (TK) and this knowledge led to the development of imatinib (STI-571), a drug that specifically inhibits the BCR-ABL TK. Common side effects of imatinib are low blood counts, nausea and vomiting, edema (swelling of the face, feet, and hands), muscle cramps and bone pain, diarrhea, hemorrhage, skin rash, and fever. Headache, fatigue, joint pain, indigestion, and abdominal pain are occasionally seen, and liver toxicity is a rare complication. We here report a case of multiple small bowel perforations in a patient of Ph+ve chronic myeloid leukemia-chronic phase on imatinib. Bowel perforation is a known complication for targeted therapy agents like bevacizumab, sunitinib, and sorafenib, which act on vascular endothelial growth factor receptor but imatinib having no anti VEGF receptor activity leading to such complication is a mystery. Physician treating their patient with imatinib should be aware of this complication and should act accordingly.
Keywords: Antivascular endothelial growth factor receptor; bowel perforation; chronic myeloid leukemia; imatinib; tyrosine-kinase inhibitor